Odpowiedzi

Najlepsza Odpowiedź!
2010-01-12T19:23:00+01:00
A)-2x+4=5x+25
-2x-5x=25-4
-7x=24/:(-7)
x=-4
b) 7y-8=-y+24
7y+y=24+8
8y=32/:8
y=4
c)6-5x=2x-7
-5x-2x=-7-6
-7x=-13/:(-7)
x=7/13

a)5x+4=4x-11
5x-4x=-11-4
x=-15
b)6y-1=y+9
6y-y=9+1
5y=10/:5
y=2
c)-2z+5=3z-25
-2z-3z=-25-5
-5z=-30/:(-5)
z=6

a)0,4z-1=0,5
0,4z=0,5+1
0,4z=1,5/:0,4
z=3,75

Wszystko rozpisałem, żebyś wiedział, co z czego się wzięło, pozdrawiam :)
2010-01-12T19:31:57+01:00
1.
a)
-2x+4=5x+25
-2x-5x=25-4
-7x=21|:(-7)
x=-3

b)
7y-8=-y+24
7y+y=24+8
8y=32:8
y=4

c)
6-5x=2x-7
-5x-2x=-7-6
-7x=-13|:(-7)
x=1⁶/₇

2.
a)
5x+4=4x-11
5x-4x=-11-4
x=-15
spr:
5*(-15)+4=4*(-15)-11
-75+4=-75-11
-71≠-86 sprzeczne

b)
6y-1=y+9
6y-y=9+1
5y=10:5
y=2
spr:
6*2-1=2+9
11=11

c)
-2z+5=3z-25
-2z-3z=-25-5
-5z=-30|:(-5)
z=6
spr:
-2*6+5=3*6-25
-12+5=18-25
-7=-7

rozwiąż równanie:
a)
0,4z-1=0,5
0,4z=0,5+1
0,4z=1,5|:0,4
z=,75